Sustainable milk-based postbiotics beverages fermented by Lactobacillus plantarum: allies in celiac disease inflammation - Bellomo, Claudia; Mauriello, Francesca; Nigro, Federica; Passannanti, Francesca; Colucci Cante, Rosa; Nigro, Roberto; Barone, Maria Vittoria; Nanayakkara, Merlin (Frontiers in Nutrition, 2025)
BackgroundCeliac disease (CeD) is an autoimmune disorder characterized by damage to the small intestine that occurs in genetically predisposed individuals after gluten consumption. Dietary exclusion is the only treatment. Gliadin is one of the main protein component of wheat gluten, and is poorly digested. Undigested peptide, p31-43, triggers several different processes, including inflammation. Intestinal organoids from CeD biopsies are good models for studying CeD inflammation. Postbiotics have been shown to modulate the effects of p31-43 in Caco-2 cells and inflammation in CeD organoids. The aims of this study was to study the anti-inflammatory activity of milk-based postbiotics from of L. plantarum.MethodsPostbiotics from L. plantarum CECT 749-fermented milk enriched with LA (linoleic acid), SCGs (Spent Coffee Grounds) and SCG oil were produced. Gliadin peptide p31-43 was used to induce inflammation on Caco2 cells. Organoids were derived from intestinal biopsies of 3 controls (CTRs) and 3 GCD (gluten containing diet)-CeD patients. NF-kB activation, a marker of inflammation, was evaluated by Western Blot analysis.ResultsThe results showed that pretreatment with all milk-based postbiotics of L. plantarum, except for SCG oil, inhibited the activation of NF-kB in the presence of the gliadin peptide in Caco-2 cells. The most efficient postbiotics, namely, milk-based postbiotics of L. plantarum with or without SCGs, could also reduce inflammation in intestinal organoids from CeD patients.ConclusionMilk-based postbiotics of L. plantarum, with or without SCGs, prevents the proinflammatory effects of gliadin on Caco-2 cells and constitutive inflammation in CeD intestinal organoids, independent of the CLA (Conjugated linoleic acid) concentration.